The mental health and well‐being of adults with intellectual disability during the COVID‐19 pandemic: A narrative review. Issue 1 (25th February 2022) - Lunsky, Yona; Jahoda, Andrew; Navas, Patricia; Campanella, Sabrina; Havercamp, Susan M.
Abstract: Prior to the start of the pandemic, adults with intellectual disability (ID) were more likely to experience mental health difficulties and face barriers obtaining mental health care. COVID‐related public health restrictions, combined with heightened challenges to obtain timely mental health care, have served to worsen this situation internationally, with a combination of new onset conditions and worsening mental health for those already struggling. In this narrative review, we summarize literature on the mental health of adults with ID during the COVID‐19 pandemic to describe what is known based on clinician perceptions, existing administrative health data, family and staff perceptions, and self‐report. In addition to noting similarities and differences in findings based on the source of information, we also explored how experiences differed depending on where and when the research was conducted. Based primarily on research conducted during the first six months of the pandemic, there is a consistent finding across sources of increased anxiety, stress, and isolation. This review also explored the delivery of virtual mental health care and the impact of pandemic‐based mental health interventions. There have been very few research studies evaluating clinical care during this time but clinicians have managed to provide supports virtually, which has been evaluated positively by some individuals. This narrative review concludes by identifying gaps in the literature and suggests key directions for future mental health research, policy, and practice efforts. Any mental health efforts now and during pandemic recovery need to have an understanding of how the mental health needs and services for adults with ID have evolved over the course of the pandemic. Further research is needed on the impact of both clinical interventions and other nonclinical efforts on the mental health of people with ID.